2014
DOI: 10.1021/cs5000284
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Cross-Coupling Reactions at Lower Temperatures Using a Photocatalyst of Palladium and Gold Alloy Nanoparticles

Abstract: Palladium (Pd)-catalyzed cross-coupling reactions are among the most important methods in organic synthesis. We report the discovery of highly efficient and green photocatalytic processes by which cross-coupling reactions, including Sonogashira, Stille, Hiyama, Ullmann, and Buchwald−Hartwig reactions, can be driven with visible light at temperatures slightly above room temperature using alloy nanoparticles of gold and Pd on zirconium oxide, thus achieving high yields. The alloy nanoparticles absorb visible lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
169
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(172 citation statements)
references
References 64 publications
3
169
0
Order By: Relevance
“…16,17,26 Aer the excitation of surface plasmons, they can decay non-radiatively via generation of hot electrons in the metal nanoparticles. The energy of these hot electrons is either redistributed among the ground state electrons through electron-electron scattering or dissipated in the form of heat by electron-phonon scattering.…”
Section: 26mentioning
confidence: 99%
See 4 more Smart Citations
“…16,17,26 Aer the excitation of surface plasmons, they can decay non-radiatively via generation of hot electrons in the metal nanoparticles. The energy of these hot electrons is either redistributed among the ground state electrons through electron-electron scattering or dissipated in the form of heat by electron-phonon scattering.…”
Section: 26mentioning
confidence: 99%
“…As a result of this transfer, the number of active catalytic sites on Pd increases, and this improves the overall rate of the reaction. 16 Such hot electron transfer from Au to Pd was described by recording a single particle photoluminescence (PL) spectra from an Au-Pd nanorod and an Au nanorod. 35 The authors observed a decrease in the PL intensity for the AuPd nanorod compared to the Au nanorod, which was attributed to hot electron transfer from Au and Pd.…”
Section: 26mentioning
confidence: 99%
See 3 more Smart Citations